«ARALQUM» TOǴAYZARLÍQQA AYLANBAQTA - Baltabaev, M.T.; Baltabaeva, V.M.; Karlıbayeva, M. (ILIM hám JÁMIYET, 2022)
The article the presents the new information about the forests created in the Aralkum. It is obvious that at the bottom of the dried-up sea in the near future there will be vast, rich in vegetation, forests and pastures. It is believed that the dried bottom of the Aral Sea will be the main area for the development of cattle breeding in the region. The article provides new information on the forests being created in the Aralkum.